Trait divergence and opposite above- and below-ground strategies facilitate moso bamboo invasion into subtropical evergreen broadleaf forest - Yu, Hua; Le, Xingui; Peñuelas, Josep; Sardans, Jordi; Xu, Chaobin; Zou, Yuxing; Zhang, Xue; Li, Conghui; Mao, Zhenwei; Cheng, Dongliang; Zhong, Quanlin (Frontiers in Plant Science, 2024)
Understanding the invasion of moso bamboo (Phyllostachys edulis) into adjacent evergreen broadleaf forest based on functional traits is crucial due to its significant influence on ecosystem processes. However, existing research has primarily focused on above-or below-ground traits in isolation, lacking a comprehensive integration of both. In this study, we conducted a trait-based analysis including 23 leaf traits and 11 root traits in three forest types -bamboo forest, mixed bamboo and broadleaf forest, and evergreen broadleaf forest -to investigate trait differences, phenotypic integration, and above-and below-ground resource strategies in bamboo and broadleaf species. Our findings demonstrated significant differences in leaf and root key traits between bamboo and broadleaf species, strongly supporting the "phenotypic divergence hypothesis". Bamboo exhibited stronger trait correlations compared to broadleaf species, indicating higher phenotypic integration. Above-and below-ground strategies were characterized by trade-offs rather than coordination, resulting in a multidimensional trait syndrome. Specifically, a unidimensional leaf economics spectrum revealed that bamboo with higher leaf N concentrations (LNC), P concentrations (LPC), and specific leaf area (SLA) adopted a "fast acquisitive" above-ground strategy, while broadleaf species with thicker leaves employed a "slow conservative" above-ground strategy. A two-dimensional root trait syndrome indicated a "conservation" gradient with bamboo adopting a "slow conservative" below-ground strategy associated with higher root tissue density (RTD), and broadleaf species exhibiting a "fast acquisitive" below-ground strategy linked to higher root N concentrations (RNC) and P concentrations (RPC), and a "collaboration" gradient probably ranging from broadleaf species with a "do-it-yourself" strategy characterized by high specific root length (SRL), to bamboo adopting an "outsourcing" strategy with thicker roots. In conclusion, key trait divergence from coexisting broadleaf species, higher phenotypic integration, and multi-dimensional opposite above-and below-ground resource strategies confer competitive advantages to moso bamboo, shedding light on the mechanistic understanding of its invasion into subtropical evergreen broadleaf forest and providing theoretical guidance for maintaining the stability of subtropical forest ecosystem.